HUBUNGANANTARA PENGETAHUAN AKSEPTOR KONTRASEPSI PILTENTANG KB PIL DENGAN KEPATUHAN AKSEPTOR DALAMMENGKONSUMSI KB PILDI DESA PASINGGANGAN KABUPATEN BANYUMAS - Kartika Sari; Prasanti Adriani (Viva Medika, 2011)
Each pill acceptors should have a good knowledge about thecontraceptive pill. So has the adherence to the pill regularly every day. Pill ifconsumed regularly, the effectiveness is quite high, but if consumed regularly candecrease the effectiveness. In everyday use due to the human error factor (forgot),then failure can be 6-8 pregnancy / 100 women users / year usage. A frequentmistake is to forget to swallow pills or late start of the new packaging. To determine the relationship between knowledge of family planningacceptors of contraceptive pills pills with compliance KB acceptors in consumingthe pills in the village Pasinggangan Banyumas in 2010 This research is an analytic correlation with cross sectional approach.The sample used is purposive sampling, samples of this study are all familyplanning acceptors pills. Samples in this study of 50 respondents From the results, the majority of respondents' knowledge was prettymuch as 28 respondents (56%), the majority of respondents dutifully taking birthcontrol pills as much as 34 respondents (68%), there is a relationship betweenknowledge acceptor pills of birth control pills with compliance acceptor inconsuming birth control pills in the village Pasinggangan Banyumas in 2010 withÃ¾-value (0.032) <Î± (0.05), then Ho is rejected and Ha accepted. There is a relationship of knowledge of family planning acceptors ofcontraceptive pills pills with compliance KB acceptors in consuming pills Keywords: Knowledge, Compliance, Consuming, birth control pills, Acceptors